Implementation and Evaluation of a Peer Mentorship Program in a Linguistic-Minority Setting - Riffel, Cassidy; Savard, Julie; Mitchell, Teaghan; Girard, Rhéanne; Gauthier, Ariane; de Moissac, Danielle; Avanthay Strus, Jacqueline (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2026)
Nursing students face a unique combination of academic, clinical, and personal stressors that place them at heightened risk for psychological distress compared to peers in other disciplines. These stressors include heavy workloads, fear of failure, emotional strain in clinical settings, and challenges transitioning from secondary school. A recent study (de Moissac et al., 2022) conducted among students at a school of nursing in Western Canada in both Canadian official languages confirmed these trends, revealing higher rates of anxiety, sleep disturbances, and self-medication among francophone nursing students. In response, a mentorship program was developed to support first-year nursing students.The purpose of this paper is to describe the process of designing the program using a community-based participatory action framework and a logic model that guided planning, implementation, and evaluation. A comprehensive evaluation toolkit supported iterative assessment and informed decision-making throughout the program’s delivery.Results from the first 2 years indicate that all short-, medium-, and long-term outcomes were achieved. The pilot phase included five mentors and 15 mentees; following improved recruitment strategies and collaboration with the school of nursing’s student club, participation increased to 42 mentees the following year. Early recruitment during orientation was key to maximizing engagement. Although the COVID-19 pandemic limited in-person interaction, virtual meetings provided academic support and connection.Mentors reported increased confidence after completing standardized education, which equipped them with leadership and problem-solving skills. The introduction of a lead mentor role further enhanced coordination and communication between students, faculty, and program coordinators. Lastly, mentees were able to gain support from their peers as they entered their first year of nursing practice and had the opportunity to be integrated into the university community early on.Challenges included limited initial awareness of the program among faculty and temporary disruption in external partner support due to staffing changes. These issues were addressed through staff meetings and re-engagement with the external agency, which now provides on-call support.Overall, the mentorship program demonstrated strong potential to enhance student well-being, leadership development, and academic success in a minority-language nursing education context.